2008
DOI: 10.4161/cc.7.16.6533
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of miR-34a by aberrant CpG methylation in multiple types of cancer

Abstract: Recently, we and others identified the microRNA miR-34a as a target of the tumor suppressor gene product p53. Ectopic miR-34a induces a G 1 cell cycle arrest, senescence and apoptosis. Here we report that miR-34a expression is silenced in several types of cancer due to aberrant CpG methylation of its promoter. 19 out of 24 (79.1%) primary prostate carcinomas displayed CpG methylation of the miR-34a promoter and concomitant loss of miR-34a expression. CpG methylation of the miR-34a promoter was also detected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
550
4
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 727 publications
(580 citation statements)
references
References 30 publications
17
550
4
6
Order By: Relevance
“…Epigenetic regulation by CpG methylation of these miRs could be cell line specific or other epigenetic mechanisms and specific transcriptional factors might interfere with the expression. Bisulfite conversion and methylation-specific PCR supported the existing data and also revealed that miR-34a, miR-199a1, miR-199a2 and miR-199b promoters were hyper-methylated and inversely correlated with their expression in a panel of cancer cells (Lodygin et al, 2008;Garzia et al, 2009;Cheung et al, 2010). Our data shows in particular that miR-199a1 and miR-199b promoters were hypermethylated in NSCLC, BRC and CRC cell lines.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Epigenetic regulation by CpG methylation of these miRs could be cell line specific or other epigenetic mechanisms and specific transcriptional factors might interfere with the expression. Bisulfite conversion and methylation-specific PCR supported the existing data and also revealed that miR-34a, miR-199a1, miR-199a2 and miR-199b promoters were hyper-methylated and inversely correlated with their expression in a panel of cancer cells (Lodygin et al, 2008;Garzia et al, 2009;Cheung et al, 2010). Our data shows in particular that miR-199a1 and miR-199b promoters were hypermethylated in NSCLC, BRC and CRC cell lines.…”
Section: Discussionsupporting
confidence: 86%
“…In general, it implies different stages of controlling mechanisms of a gene, especially of an oncogene. Moreover, miR-34a and miR-199a2 are reported that they are epigenetically controlled by CpG methylation (Lodygin et al, 2008;Cheung et al, 2010). 5-Aza treatment significantly induced the expression of either one or all of the miRs (miR-34a, miR-199a and b) in the screened cell lines.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A literature search using MEDLINE revealed that 16 miRNAs are known to be epigenetically silenced by DNA methylation [8], [9], [10], [11], [12], [13], [14], [15], [16], [17]. DNA methylation refers to the covalent addition of a methyl group to the 5-position of cytosines, usually in a CpG dinucleotide context in mammalian differentiated cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…miR-34a commonly functions as a tumor suppressor and is down-regulated in many human cancers [11]. Previous studies have revealed that miR-34a is regulated by p53, a tumor suppressor gene [12,13].…”
Section: Micrornas (Mirnas) An Evolutionarily Conserved Class Of Endmentioning
confidence: 99%